Peningkatan Literasi Keuangan Siswa SMA melalui Sosialisasi Risiko Penggunaan PayLater di Bandar Lampung - Hani Damayanti Aprilia (Ragom Jurnal Pengabdian Masyarakat, 2026)
ABSTRACT The development of digital financial services, especially payLater, provides convenience in transactions, but also has the potential to pose financial risks for users, especially the younger generation. Low financial literacy in students is one of the factors that encourages the unwise use of payLater. Therefore, this community service activity aims to improve students' financial literacy through the socialization of the risks of using payLater. The activity was carried out at SMA 2 Perintis Bandar Lampung with an educational-participatory method which included lectures, discussions, and case studies. Evaluation was carried out using pre-test and post-test. The results of the activity showed an increase in student understanding which was marked by an increase in score from 500 in the pre-test to 1900 in the post-test, as well as an average N-Gain score of 0.71 which was included in the high category. This shows that socialization activities are very effective in improving students' financial literacy. Thus, this activity is expected to form a wiser attitude in the use of digital financial services among students. Keywords: community service, financial literacy, fintech, high school students, payLater,